Pengembangan Perpustakaan Digital Universitas Riau Dengan Program Library Management System (Slims) - Yuli Astuti; Nurasmi (Perpustakaan Universitas Riau, 2013)
Along with the times, as well as an abundance of information obtained, so the information available at this time may not be accommodated in the library or documentation center and any information. Technological developments especially in the field of electronics and telecommunications are in line with the growth of information having helped solve this problem. Developments in technology have given rise to a new form library, the digital library. The development of digital libraries in Indonesia is encouraging, although it is still in the testing phase and development. In order to develop a digital library, a lot of software can be used, for example Winisis, GDLS, GSDLS and others. But at Riau University library program is selected for the program applied Senayan Library Management System (Slims). SliMS is a work of the nation. Its applications built using PHP language program and MYSQL database with the Git version control. 2009 Slims got the first level in the event INAICTA 2009 for open source. Currently SliMS has been used extensively by various libraries, both in Indonesia and abroad.